PEMBERIAN PUPUK ORGANIK SEBAGAI CAMPURAN MEDIA TUMBUH BABY KAILAN (Brassica oleracea L.) SECARA VERTIKULTUR - Sri Yoseva; Sheibila Naqi Alfadillah; Murniati (DINAMIKA PERTANIAN, 2021)
The research aims to determine the effect of the addition of some organic fertilizers as a mixed growing medium for growth and yield of baby kailan and to get the best type of organic fertilizer to support the growth and yield of baby kailan plants in viticulture. The research was carried out at the the Experimental farm of the Agriculture Faculty, Riau University. The research took time four months, starting from February to May 2019 and the experiment, which consisted of four treatments and arranged using a completely randomized block design (RBD) of organic fertilizer, consisted of Cow manure, Goat manure, Chicken manure, and Oil Palm Empty Fruit Bunches (OPEFB) compost. The observed parameters were plant height (cm), number of leaves (strands), fresh weight per plant (g), plant weight for consumption per plant (g), and root volume (ml). The observational data were analysed using the Statistical Analysis System (SAS) program. The results showed that the OPEFB compost treatment provided the best for the growth and yield of baby kailan. OPEFB compost gave the best results for all parameters.